Otherwise engaged [large type] - Mallery, Susan (Thorndike Press large print dynamic drama., 2025)
"When Shannon gets engaged, her mom Cindy is the first person she wants to tell--and the last. Cindy's engaged, too, and has hinted at a double wedding. Victoria has never been enough for her mother Ava, so she stopped trying. Chance brings the four women together, where a shocking secret comes out. Twenty-four years ago, desperate teenager Cindy chose wealthy Ava to adopt her baby--then changed her mind at the last second. The loss rocked Ava's world, leaving her unable to open her heart to the daughter she did adopt, Victoria"--